THE COMPARISON OF READING COMPREHENSION TAUGHT BY USING STAD AND JIGSAW TECHNIQUE AT DIFFERENT MOTIVATION TO READ AT THE EVEN SEMESTER OF ELEVENTH GRADES IN SMAN 1 RUMBIA ACADEMIC YEAR 2012/2013 - Eko Mulyono; Bambang Eko Siagianto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
Reading is necessary when students further their study, especially at Senior High School level. Based on the Pre survey, Many students are not interested in reading subject, the students are not interested in teaching technique which is used by the teacher, the students motivation to read are still low, the quality of their reading comprehension are still low. There are two techniques presented as a solution in this research. They are STAD Technique and Jigsaw technique. The objective of this research is to know whether there is any difference of reading comprehension taught by using STAD and Jigsaw technique,to unlock whether there is any difference of reading comprehension taught by using STAD and Jigsaw technique at high and low motivation to read, and to explore whether there is any interaction of reading comprehension, learning technique, and different motivation to read at the even semester of eleventh grades in SMA N 1 Rumbia academic year 2012/2013.The method of investigation is held through quantitative research. The researcher uses true experimental research. In this experiment, the researcher applies factorial design. The research is conducted at the eleventh grades of SMA N 1 Rumbia in academic year 2012/2013. The population in this research is 204 students. It consisted 6 classes and each class consist 34 students. The researcher takes 68 students from total population as the sample, 31 students as experiment class and 31 as control class that match based on classification of student level. The researcher uses cluster random sampling as technique sampling.To analyze data, the researcher uses ANOVA TWO WAYS formula. The researcher got the result of Fhit is 18, 2 and Ftable is 7, 14. It means that Fhit > Ftable. And the criterion of Ftest is Ha accepted if Fhit > Ftable. So, there is any difference result of Reading comprehension taught by using STAD and Jigsaw and STAD technique is more effective technique than Jigsaw technique toward students Reading comprehension at different motivation to read at the eleventh grades of SMA N 1 Rumbia academic year 2012/2013. The researcher expects English teacher use STAD Technique in reading, so the students feel fun and enjoy in following the learning process.